UNJUK KERJA MESIN LAS GESEK ROTARY PADA BAJA KERBON RENDAH DILIHAT DARI STRUKTUR MAKRO DAN UJI BENDING - Hafni, Hafni; Wardianto, Dedi (ITP Press, 2024)
Friction welding is a welding process that produces fusion through heat generated between two joint surfaces due to the mechanical movement of the rubbing surfaces. The heat produced due to surface friction is very dependent on the number of rotations of the driving motor.Testing of this rotary type friction welding machine was carried out in the Mechanical Engineering laboratory of the Padang Institute of Technology. The friction welding machine has a motor power of 2 HP producing 3950 rpm rotation at the chuck and the connection press uses a hydraulic jack and is equipped with a braking system which functions to stop the motor rotation after the connection occurs with a braking time of 1.1 seconds.The test material used is low carbon steel with a diameter of 10 mm and a diameter of 8 mm, the length of the test material is 8 cm. The amount of test material with a diameter of 10 mm is 6 rods. And the number of test materials with a diameter of 8 mm was 6 rods. The surfaces of the test materials being joined must be flat and clean from rust or other chemical substances that could damage the connection.The results of tests carried out on steel bars with a diameter of 10 mm with an initial length of 16 cm with three tests obtained an average final length of 15.5 cm with an average total welding time of 79 seconds and a time for heat generation and pressure of 20 seconds, a large pressing force of 196 N. On the test material with a diameter of 8 mm, an initial length of 16 cm with three tests obtained an average final length of 15.5 cm and a total welding time of 49 seconds, heat time of seconds, pressing force of 157 NFrom the macro structure tests and bending tests, it shows good b=mechanical properties where in the test samples there are no breaks or cracks in the nugget joints formed. Keywords: Rotation, heating time,